The mediating role of employee creativity in the relationship between job self-efficacy and entrepreneurship of education and training staff in Birjand - Mansour Allah Yar (Institute of Management fekrenoandish, 2020)
The aim of this study was to determine the mediating role of employee creativity in the relationship between job self-efficacy and entrepreneurship of education and training staff in Birjand. The research method was correlational. The statistical population of this study included all the training staff of Birjand city in the academic year of 2009-2010. Based on Karajsi and Morgan table (1970), 234 samples were selected by cluster sampling method. Data collection tools were Riggs & Knight's Self-Efficacy Questionnaire (1994), Redsip's Creativity Questionnaire (1979), and Hill's Organizational Entrepreneurship Questionnaire (2003). Data analysis using structural equation model showed that the fitness indicators are in the desired level. This shows the appropriate fitness of the role model of employee creativity in the relationship between job self-efficacy and entrepreneurship of education and training staff in Birjand. There is also a relationship between job self-efficacy and entrepreneurship of Birjand education and training staff. There is a relationship between employee creativity and entrepreneurship of Birjand education and training staff.